Current Pharmacological Intervention and Medical Management for Diabetic Kidney Transplant Recipients - Theerawut Klangjareonchai; Natsuki Eguchi; Ekamol Tantisattamo; Antoney J. Ferrey; Uttam Reddy; Donald C. Dafoe; Hirohito Ichii (MDPI AG, 2021)
Hyperglycemia after kidney transplantation is common in both diabetic and non-diabetic patients. Both pretransplant and post-transplant diabetes mellitus are associated with increased kidney allograft failure and mortality. Glucose management may be challenging for kidney transplant recipients. The pathophysiology and pattern of hyperglycemia in patients following kidney transplantation is different from those with type 2 diabetes mellitus. In patients with pre-existing and post-transplant diabetes mellitus, there is limited data on the management of hyperglycemia after kidney transplantation. The following article discusses the nomenclature and diagnosis of pre- and post-transplant diabetes mellitus, the impact of transplant-related hyperglycemia on patient and kidney allograft outcomes, risk factors and potential pathogenic mechanisms of hyperglycemia after kidney transplantation, glucose management before and after transplantation, and modalities for prevention of post-transplant diabetes mellitus.